외안근 Expander 로서의 Gore-Tex 의 유용성에 대한 실험적 연구 - 김한규; Han Gyu Kim; 남희; Hee Nam; 유지명; Ji Myong Yoo; 송준경; Joon Kyeong Song (Daihan angwa haghoi jabji, 1996)
Expander 삽입술은 새로운 외안근 약화술로 절단면의 조절과 재수술이 용이하고, 술후 근육 기능 저하의 빈도가 낮은 장점을 갖고 있다. 저자들은 외안근 expander로서의 Gore-Tex의 유용성을 알아보고자, 15마리 가토의 상사근에 Gore-Tex(우안)와 silicone retinal band(좌안)를 삽입한 후 1주, 3주, 5주, 7주, 12주에 병리조직학적 변화를 관찰하였다. 염증소견은 두 군간에 거의 차이가 없었으며 시간이 지나면서 두 군 모두에서 감소하였다. Gore-Tex expander를 사용한 군에서는 술후 3주째부터 절단면으로부터 근육 재생이 생겨 진행하였고, 술후 5주째부터 expander 내로 섬유 모세포의 ingrowth가 관찰되었다. 두 군 모두에서 공막과 expander 간의 직접적인 유착은 관찰되지 않았다. 이상의 결과로 보아 Gore-Tex가 외안근 화약술을 위한 expander로 사용하기에 적합할 것으로 생각된다(한안지 37:1186∼1195, 1996). Expander procedure is a newly developed extraocular muscle weakening technique which has several advantages such as good control of resection margin, easy reoperation, rare postoperative muscular paresis. For the study of usability of Gore-Tex as a muscle expander, fifteen rabbits received expander procedure with Gore-Tex in right eye and silicone retinal band in left eye. At postoperative 1, 3, 5, 7, 12 weeks, histopathologic examination was performed. There was no significant difference in inflammatory reaction in both groups. Inflammatory reaction decreased with time in both Groups. In Gore-Tex expander group, muscle regeneration from cut end was observed at the 3rd postoperative week and fibroblast ingrowth into the expander was observed at the 5th postoperative week. These findings were more prominent with time. Adhesion of expander to underlying sclera was not observed in both groups. It is concluded that expander procedure using Gore-Tex will be a new and useful surgical method for the extraocular muscle weakening procedure(J Korean Ophthalmol Soc 37:1186∼1195, 1996).